MORFOLOGI TASGHIR DALAM BAHASA ARAB DAN KONTRIBUSINYA TERHADAP PEMAHAMAN NUANSA MAKNA DALAM HADIS NABI - Intan Nazmi Nurlaila (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore the morphological phenomenon of tasghīr in Arabic and its contribution to understanding the nuanced meanings within the sayings (ḥadīths) of the Prophet Muhammad ﷺ. Tasghīr, often translated as